Lost Logarithm IV

Algebra Level 3

2 log 4 200 0 6 + 3 log 5 200 0 6 \large \dfrac 2{\log_4{2000^6}} + \dfrac 3{\log_5{2000^6}}

The number above can be written as m n \dfrac mn where m m and n n are relatively prime positive integers. Find m + n m + n .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Danish Ahmed
Apr 25, 2015

We know that 1 log a b = log b a \dfrac 1{\log_a{b}} = \log_b{a}

2 log 4 200 0 6 + 3 log 5 200 0 6 = 2 1 log 4 200 0 6 + 3 1 log 5 200 0 6 = 2 log 200 0 6 4 + 3 log 200 0 6 5 = log 200 0 6 4 2 + log 200 0 6 5 3 = log 200 0 6 4 2 5 3 = log 200 0 6 2000 = 1 6 . \begin{aligned} \dfrac 2{\log_4{2000^6}} + \dfrac 3{\log_5{2000^6}} &= 2 \cdot \dfrac{1}{\log_4{2000^6}} + 3\cdot \dfrac {1}{\log_5{2000^6} }\\ &=2{\log_{2000^6}{4}} + 3{\log_{2000^6}{5}} \\ &={\log_{2000^6}{4^2}} + {\log_{2000^6}{5^3}}\\ &={\log_{2000^6}{4^2 \cdot 5^3}}\\ &={\log_{2000^6}{2000}}\\ &= {\frac{1}{6}}.\end{aligned}

Therefore our answer is 1 + 6 = 7 1 + 6 = \boxed{7} .

Joel Yip
Apr 26, 2015

First, 2 log 4 2000 6 + 3 log 5 2000 6 = 2 6 log 4 2000 + 3 6 log 5 2000 = 1 3 log 4 2000 + 1 2 log 5 2000 \frac { 2 }{ \log _{ 4 }{ { 2000 }^{ 6 } } } +\frac { 3 }{ \log _{ 5 }{ { 2000 }^{ 6 } } } \\ =\frac { 2 }{ 6\log _{ 4 }{ 2000 } } +\frac { 3 }{ 6\log _{ 5 }{ { 2000 } } } \\ =\frac { 1 }{ 3\log _{ 4 }{ 2000 } } +\frac { 1 }{ 2\log _{ 5 }{ { 2000 } } } \\

After some things, we get 1 3 ( 2 + 3 log 4 5 ) + 1 2 ( 3 + 2 log 5 4 ) \\ \frac { 1 }{ 3\left( 2+3\log _{ 4 }{ 5 } \right) } +\frac { 1 }{ 2\left( 3+2\log _{ 5 }{ 4 } \right) } \\

Let log 5 4 \log _{ 5 }{ 4 } \\ be x x

1 3 ( 2 + 3 x ) + 1 2 ( 3 + 2 x ) = 3 ( 2 + 3 x ) + 2 ( 3 + 2 x ) 6 ( 3 + 2 x ) ( 2 + 3 x ) = 6 + 9 x + 6 + 4 x 6 ( 6 + 9 x + 6 + 4 x ) = 1 6 \\ \frac { 1 }{ 3\left( 2+\frac { 3 }{ x } \right) } +\frac { 1 }{ 2\left( 3+2x \right) } \\ =\frac { 3\left( 2+\frac { 3 }{ x } \right) +2\left( 3+2x \right) }{ 6\left( 3+2x \right) \left( 2+\frac { 3 }{ x } \right) } \\ =\frac { 6+\frac { 9 }{ x } +6+4x }{ 6\left( 6+\frac { 9 }{ x } +6+4x \right) } \\ =\frac { 1 }{ 6 }

so the answer is 7 \boxed{\boxed{\boxed{\boxed{7}}}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...